A strengths-based social skills development strategy:a case study of a student with autism spectrum disorder - Kaffemanienė, Irena; Jurevičienė, Margarita; Gindulytė, Kornelija (Special Education, 2025)
This case study explored the possibilities of applying strengths-based strategies to develop the social skills of a student with autism spectrum disorder. Problem questions: What peculiarities (strengths, deficiencies) of social skills in the student with autism spectrum disorder do the student’s educators envisage? What are the opportunities for developing this student’s social skills, based on the perspective of strengths? The aim of the research - using a case analysis to determine the possibilities of applying a strengths-based social skills development strategy to a student with autism spectrum disorder. Research methodology and methods: theoretical analysis; case studies (semi-structured interviews; modeling of an individualized social skills development plan; focus group survey and content analysis). Study sample. An 8-year-old special school student with autism spectrum disorder was selected for the case study. Other participants of the study were the student’s educators (teachers, speech therapist, the child’s parents, etc.). After qualitative content analysis of semi-structured interview data, the strengths (functionality) of social skills of a student with autism spectrum disorder were determined. An individual social skills development plan based on the student’s strengths was modeled through group discussions with teachers and the student’s parents. The study participants developed the student’s social skills for 3 months according to this plan. Based on the prepared plan, the student’s social skills were developed at school and in the family, applying the social skills group training model, when, under the guidance of adults (teachers, parents), the child, together with peers, engages in joint activities. The results of the strengths-based social skills development were analyzed using the focus group method. A slight increase in the functionality of some social skills was determined (the child’s greater interest in peers and participation in joint activities with peers, better concentration of attention, etc.). In addition, according to the study participants, positive changes occurred in the areas of teacher-parent cooperation and understanding of the student’s individual needs.